Towards the Prosperity of Small Business Enterprises: What’s in for Information and Communication Technology? - Liliane Pasape (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
Small business enterprises, or SBEs, are often defined by their small size, limited resources, and low employee count. Some of them were given access to incubation programs, which provide access to working space, business capacity building, networking, mentoring, and business development support services in order to overcome those problems during the early phases of business operations. This study looked at how information and communication technology (ICT) can help SBEs in Tanzania that have been subjected to incubation programs improve their business performance. Purposive sampling was used to collect primary data from fifty SBEs undergoing incubation programs at the Tanzania Engineering and Manufacturing Development Organization, one of the government facilities. The data was analyzed using the Statistical Package for Social Science and the R Programming Language. The results showed that incorporating ICT into day-to-day activities improves access to business information, increases market overage and market share, strengthens marketing promotion efforts, and reduces financial difficulties by over 70%. In terms of increasing output from business operations, the findings revealed that the use of ICT is likely to improve business performance by creating a favorable business environment, reducing business-related obstacles, and shortening the time it takes to bring new products to market for 64 percent, 78 percent, and 72 percent of respondents, respectively. Improving corporate efficiency is a side effect rather than a direct result. Furthermore, using ICT, incubated SBEs have a significant possibility of growing the number of products sold, the quantity of money earned, and profit margin by more than 60%. Nonetheless, the impact of ICT on the ability to sell firm assets on the open market is just 52%. As a result, despite their limited resources, incubated SBEs must try to integrate ICT-mediated technology into their operations.